Peran Pendidikan Agama Kristen dalam Membangun Budaya Damai dan Resolusi Konflik di Kalangan Remaja - Nofita R. Asbanu; Daud Saleh Luji (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Adolescents are an age group that is vulnerable to social conflict due to emotional immaturity and the search for self-identity. Amidst the increasing cases of violence and intolerance among adolescents, Christian Religious Education (PAK) has strategic potential in forming peaceful characters and constructive conflict resolution skills. This study uses a descriptive qualitative approach through an in-depth literature review of various literature and scientific journals from the last five to ten years. The results of the study indicate that PAK plays a role in internalizing the values ​​of love, forgiveness, tolerance, and justice that are relevant to building a culture of peace. In addition, PAK also contributes to forming a healthy social identity among adolescents, strengthening multicultural awareness, and providing skills in resolving conflicts non-violently. The instillation of these values ​​is carried out through a holistic approach that includes cognitive, affective, and practical learning. Christian Religious Education not only forms religious understanding, but also plays a role as a means of social transformation amidst the complex reality of conflict. Thus, PAK can be an important element in efforts to prevent conflict and form a young generation with a peaceful personality. These findings are expected to be the basis for developing a curriculum and practice of Christian education that is more responsive to the social challenges faced by today's youth.